A hidden symmetry in quantum gravity - Ananth, Sudarshan (2018)
The action integral contains more information than the equations of motion. Since it is an integral, changes of the integration variables occasionally also expose symmetries more easily than working directly with the equations of motion. We have previously shown that there are signs of an extended exceptional symmetry for N=8 supergravity in four dimensions. The symmetry is such that the fields used in the Lagrangian are not representations of the symmetry. Instead one has to add representations to obtain a representation of the extended symmetry group. In this paper we discuss an extended symmetry in four-dimensional gravity which is the “Ehlers Symmetry” in three dimensions. It cannot be spanned by the helicity states of four-dimensional gravity but it can be realised once we treat the helicity states just as field variables of the functional integral, which can be changed like variables in any integral. We also explain how this symmetry is inherent in formulations of N=8 supergravity in four dimensions through a truncation in the field space to pure gravity. The establishment of these “hidden” symmetries should play an important role in the perturbative behaviour of the quantum theories. Since the method used n this paper is purely algebraic we will not provide any information on the geometric role of these symmetries.